PENINGKATAN KETERAMPILAN SANTRI MELALUI PELATIHAN PEMBUATAN DIMSUM IKAN PATIN (PANGASIUS SP.) DI PONDOK PESANTREN RAUDHATUL ULUM, SAKATIGA, INDRALAYA, KABUPATEN OGAN ILIR - Dwi Inda Sari; Irmayani Lubis, Adelina; Waldani, Dina; Lenawati Tindaon, Rotua; Tabina Yudanto, Haura; Agustia, Reza (LPPM Universitas Bina Bangsa, 2025)
This community service aims to empower teachers, students and canteen employees through improving skills in making catfish dim sum as an effort to diversify fishery-based food. This activity was carried out at Pondok Pesantren Raudhatul Ulum, Sakatiga with a training method that includes theory and practice. Patin fish was chosen as the main ingredient due to its high nutritional content and its potential in supporting the prevention of stunting in children. In addition, the training also included education on packaging and storage techniques for small-scale production. The results of the activity showed an increase in the understanding and skills of teachers and students in making catfish dim sum, as well as the potential for small business development in the school environment.